2020
DOI: 10.1111/evj.13302
|View full text |Cite
|
Sign up to set email alerts
|

Objectively measured movement asymmetry in yearling Standardbred trotters

Abstract: Background Lameness evaluation of Standardbred trotters can be challenging due to discrepancies in observed movement asymmetry between in‐hand and track exercise, and between different trotting speeds. There are few studies on objective measurement of movement in Standardbreds, and little knowledge regarding biological variation and clinical significance of measured movement asymmetry in this breed. Objectives To quantify the prevalence and magnitude of objectively measured movement asymmetry in young Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…The results showed that VS for both front and hind limbs recorded in trot in hand did not differ from VS during driving on the track. This is also in accordance with findings by Kallerud et al (2020). Observations made during trot in hand can therefore be considered useful.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that VS for both front and hind limbs recorded in trot in hand did not differ from VS during driving on the track. This is also in accordance with findings by Kallerud et al (2020). Observations made during trot in hand can therefore be considered useful.…”
Section: Discussionsupporting
confidence: 91%
“…Others have questioned the role of breed and indeed Standardbred race horses showing particular interstride variability of gait parameters. 27 Considering that interstride CV did not differ between observations, it is plausible that the horses' temperament rather than biological variability of chronic conditions was responsible for the encountered data spread. Consequently, conditioning Standardbred race horses which may be unfamiliar to trotting in hand to experimental procedures may have improved data quality and ultimately aided the detection of treatment effects.…”
Section: Discussionmentioning
confidence: 97%
“…It would have been valuable to measure the horses' movements during the exercise tests as well to investigate immediate associations between rein tension and asymmetry on a stride-by-stride basis. Recently published data showed that asymmetries recorded in-hand and when Standardbred yearlings were driven on the track did not differ significantly ( 31 ). Moreover, results from Starke et al ( 33 ) revealed no significant changes in asymmetry based on speed of trotting horses in hand on a straight line.…”
Section: Discussionmentioning
confidence: 99%